Kategori dan Fungsi Sosial Cerita Rakyat di Kenegerian Kari Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi Provinsi Riau - Sutriati, Nepi; WS, Hasanuddin; Zulfadhli, Zulfadhli (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This article was write aimed to describe the category of folklore in Kenegerian Kari Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi Province of Riau. The data of this study were category and social function of folklore in Kenegerian Kari Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi Province ofÂ  Riau. The data of the research is analyzed through the stage of inventory, classified, study and inference, and the stage of report. The findings of the study showed that the category from 8 folklore in Kenegerian Kari Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi Province ofÂ  Riau showed that, 1 myth, 1 fable, 6 legend and the social function of folklore in Kenegerian Kari showed that, (1) the function of developed the integrity of society through establishment the new myth by refused the old myth, (2) the function of social solidarity, and (3) the function of society identity.